Optimization of hydrolysis of edible bird’s nest as potential prebiotic ingredient - Tan, Hui Yan (2020)
Edible Bird’s Nest (EBN) is dried gelatinised salivary secretion from the swiftlets, Aerodramus fuciphagus and Aerodramus maximus during their breeding season. Edible bird’s nest was reported to possess various health benefits and has been widely consumed since the ancient dynasty in China with their practices of Traditional Chinese Medicine (TCM). Scientific evidence supported this statement with the nutritional content of EBN, which consists of unique and high valued glycoprotein, sialic acid, epidermal growth factor (EGF), and other components that promote anti-oxidative, anti-hypertensive, immunity and more. Today, EBN is even utilised in a broad range of industries such as food, medical, pharmaceutical, and cosmetic industries. However, the utilisation and consumption of EBN are bounded due to certain properties such as insolubility. This limitation is overcome by the invention of bioactive EBN hydrolysate which simplifies the glycoprotein into glycopeptide and free peptide with improvement in solubility, functional, and nutritional properties. In this study, cleaned house EBN underwent alcalase enzymatic hydrolysis for 1, 2, 3, and 4 hours to investigate the optimal conditions for the production of EBN hydrolysate. The degree of hydrolysis of EBN suggested that 60 – 90 minutes of alcalase treatment is sufficient to release EBN micro-particles from the inactive core protein. Through hydrolysis, the physicochemical properties of EBN showed that the macro glycoprotein and protein breakdown into glycopeptide and free peptide, while leaving the amino acid, sialic acid, and glycan part remain untouched. Further on as a food ingredient, the consumption of EBN and information regarding the digestibility and prebiotic activity of EBN remain unknown. In this research, the prebiotic potential of EBN and hydrolysate were evaluated through in vitro digestion using amylase, pepsin, pancreatin, and bile, followed by in vitro fermentation with colon model that mimics the human gastrointestinal environment. Samples obtained at 0, 6, 12, and 24 hours were evaluated for bacterial enumeration by fluorescent in situ hybridisation (FISH) and organic acids production by high-performance liquid chromatography (HPLC). The population of Bifidobacterium and Lactobacillus have demonstrated a positive prebiotic effect in EBN and hydrolysates similar to the fructooligosaccharides (FOS) that act as a positive control. The raw EBN (ER) and hydrolysate that undergo 1-hour hydrolysis (EH-1) also highlighted a significantly higher inhibition in the growth of pathogenic Clostridium histolyticum group when compared to FOS. The metabolites analysed for acetate, propionate, and butyrate showed a production similar to FOS, especially in ER and EH-1 with a regular production trend. This is the contribution of the bioactive glycan-oligosaccharides peptides in EBN that partially resists digestion of which remained intact until reaching the colon and being fermentable for colonic microbiota, leading to the prebiotic potential of EBN itself. Protein and peptide as the major nutrients in EBN were observed to contribute to low production of valerate, isovalerate and isobutyrate especially in ER and EH-1. This phenomenon has precluded the possibilities of toxicity in the colon. The study found that the EBN and hydrolysate are able to enhance colonic bacteria, promote probiotic growth, suppress pathogen and produce beneficial metabolites, therefore able to function as a prebiotic ingredient that promotes colon health.